Dislocation-graphene interactions in Cu/graphene composites and the effect of boundary conditions: a molecular dynamics study. (February 2021) - Shuang, Fei; Aifantis, Katerina E.
Abstract: In this paper, systematic molecular dynamics simulations were employed to study dislocation-graphene interactions in Cu/graphene systems using two carefully selected configurations: (i) edge dislocations in the pileup interacting with graphene during nanoindentation and (ii) complex dislocations interacting with graphene in compression of layered nanopillars. The intrinsic and extrinsic size effects were investigated with respect to varying the Cu lamella thickness and pillar sizes, revealing an anomalous extrinsic size effect: the smaller, the weaker. To understand which boundary conditions are physically consistent, both free and periodic graphene were considered. It was seen that edge dislocations in the pileup continuously transmitted across the free graphene through Cu/graphene interfacial sliding and graphene reorientation, whereas transmission was very difficult for periodic graphene as its in-plane deformation was required. In compression of Cu/graphene nanopillars, the strengthening effect of free graphene was found to be less obvious than that of the periodic case, which could be attributed to free graphene edges acting as dislocation sources after the compressed Cu overflowed the graphene sheet from all directions. We therefore conclude that the strengthening effect of periodic graphene inclusions appears to be overestimated, such that free graphene should be more appropriate. Graphical abstract: Image 1